The Perceived Value of Malls as Urban Attractions: A Study of Tourist Perceptions and Experience in Tangerang Area - Elang Kusumo; Diena Mutiara Lemy; Reagan Brian (Universitas Pelita Harapan, 2024)
Urban tourism growing rapidly around the world, with shopping centers (malls) progressively situated as urban tourism centers that coordinated retail, excitement, eating, and social encounters. This research analyzes the perceived value of shopping centers as urban attractions within the Tangerang region, centering on the transaction between tourist perceptions, tourist experience, and the affect on perceived value. Employing a quantitative investigate approach, information were collected from 150 respondents whose the shopping center guests through a organized overview. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among the variables. The results of the analysis indicate that Tourist Perception and Tourist Experience has a significant influence on Perceived Value. This study contributes to the urban tourism literature by highlighting the role of malls as multifunctional tourist attractions and providing practical recommendations for tourism planners and mall developers in Tangerang, so that malls are carefully planned and intended to be a tourist destination that produces sustainable benefits. By increasing the attractiveness of malls through improving visitor perceptions and experiences, malls as one of the urban tourist destinations will be known as attractive and most sought-after places by tourists who want to get a memorable tourist experience.